2016
DOI: 10.1093/pcp/pcw132
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activation ofRD29AVia Integration of Salinity Stress and Abscisic Acid inArabidopsis thaliana

Abstract: Plants perceive information from the surroundings and elicit appropriate molecular responses. How plants dynamically respond to combinations of external inputs is yet to be revealed, despite the detailed current knowledge of intracellular signaling pathways. We measured dynamics of Response-to-Dehydration 29A (RD29A) expression induced by single or combined NaCl and ABA treatments in Arabidopsis thaliana. RD29A expression in response to a combination of NaCl and ABA leads to unique dynamic behavior that cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…1). Accumulating evidence revealed that most of these homologous genes in Arabidopsis regulate salt and dehydration tolerances through activation of ABA-responsive network and stress-responsive genes4647484950. These evidences suggested that these MeERFs might be positively involved in drought and salt tolerances of cassava.…”
Section: Discussionmentioning
confidence: 97%
“…1). Accumulating evidence revealed that most of these homologous genes in Arabidopsis regulate salt and dehydration tolerances through activation of ABA-responsive network and stress-responsive genes4647484950. These evidences suggested that these MeERFs might be positively involved in drought and salt tolerances of cassava.…”
Section: Discussionmentioning
confidence: 97%
“…Reports have shown that AtCor15 is a chloroplast stromal protein that protects chloroplast membranes during freezing stress [ 14 , 15 , 16 ]. Further, AtCor78 , also known as AtRD29A (responsive to dehydration, RD), is involved in the response to cold, dehydration, and salt stressors [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…RD29A and its homologue, RD29B, code for enzymes unlikely to be directly involved in a protectory role in abiotic stress although their exact functions are still unknown [42]. Transcript abundance of RD29A is the highest approximately 2 h after salt treatment [16]. In our results, NaCl treatment did not induce the expression of RD29A (Figure 7).…”
Section: Bc204 Treatment Alters the Expression Of Genes Involved In Tmentioning
confidence: 45%